2007
DOI: 10.1152/ajpheart.00285.2006
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of connexin40 and increased prevalence of atrial arrhythmias in transgenic mice with cardiac-restricted overexpression of tumor necrosis factor

Abstract: Sawaya SE, Rajawat YS, Rami TG, Szalai G, Price RL, Sivasubramanian N, Mann DL, Khoury DS. Downregulation of connexin40 and increased prevalence of atrial arrhythmias in transgenic mice with cardiac-restricted overexpression of tumor necrosis factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 37 publications
1
77
1
3
Order By: Relevance
“…Western blot analysis and immunohistochemistry studies in mouse hearts overexpressing TNF-␣ do not show decreased Cx43 expression in ventricles (25,55). Immunohistochemical studies, however, show that, while in WT mice Cx43 is primarily located in the intercalated discs of cardiac myocytes, in TG mice, with cardiac-specific overexpression of TNF-␣, Cx43 is dispersed throughout the sarcolemma and in intercalated disks (55).…”
Section: Differences In Aps and Ca 2ϩ Handling In Isolated Ventriculamentioning
confidence: 89%
See 2 more Smart Citations
“…Western blot analysis and immunohistochemistry studies in mouse hearts overexpressing TNF-␣ do not show decreased Cx43 expression in ventricles (25,55). Immunohistochemical studies, however, show that, while in WT mice Cx43 is primarily located in the intercalated discs of cardiac myocytes, in TG mice, with cardiac-specific overexpression of TNF-␣, Cx43 is dispersed throughout the sarcolemma and in intercalated disks (55).…”
Section: Differences In Aps and Ca 2ϩ Handling In Isolated Ventriculamentioning
confidence: 89%
“…Conduction between ventricular myocytes depends on the excitability of cardiomyocytes and the expression and distribution of connexin43 (Cx43), which is the predominant connexin type in the mouse ventricles (55). Western blot analysis and immunohistochemistry studies in mouse hearts overexpressing TNF-␣ do not show decreased Cx43 expression in ventricles (25,55).…”
Section: Differences In Aps and Ca 2ϩ Handling In Isolated Ventriculamentioning
confidence: 99%
See 1 more Smart Citation
“…Irregular production of these proteins might alter intercellular communication, reducing conduction within the atrial myocardium and creating an arrhythmogenic substrate for AF. 46 This concept was supported by Sawaya and coworkers, 47 who achieved the downregulation of connexin 40 (but not of connexin 43) in 8 transgenic mice by means of targeted overexpression of tumor necrosis factor in the pericardium.…”
Section: Correlation Between Atrial Fibrillation and Inflammationmentioning
confidence: 93%
“…A previous study assessed inflammation of EAT that was harvested from patients undergoing cardiac surgery, and showed that it represented an important local source of the inflammatory mediators tumor necrosis factor-a and interleukin-6 [21,22], which might have direct arrhythmogenic effects on atrial tissue and be associated with AF pathogenesis [23]. Moreover, lone AF and rapid acute pacing were recently reported to provoke significant changes in atrial adipogenesis and to promote adipocyte differentiation and adipose tissue expansion [24].…”
Section: Inflammation Of Eat and Afmentioning
confidence: 99%